Hypertriglyceridemia — current status of the problem. Part I: risks, physiology and pathophysiological aspects, classification and diagnostic problems - A. A. Semenkin; A. N. Meshkov; M. V. Yezhov (Российский кардиологический журнал)
Numerous studies demonstrate an independent relationship between an increase in the blood content of triglyceride-rich particles and the risk of atherosclerotic cardiovascular diseases and acute pancreatitis. This review article presents in detail aspects of the pathogenesis of various types of primary and most relevant secondary hypertriglyceridemias (HTGs). Classifications are provided depending on the etiology, phenotype of dyslipidemia and severity. Approaches to HTG diagnosis are described. Special attention is paid to the potential of HTG therapy.